2017
DOI: 10.14309/crj.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

Acute Liver Failure from Herpes Simplex Virus in an Immunocompetent Patient Due to Direct Inoculation of the Peritoneum

Abstract: Herpes simplex virus (HSV) hepatitis is a rare cause of acute liver failure (ALF). It carries a mortality rate of 80% if untreated, thus early identification and treatment are critical. Without high clinical suspicion, HSV hepatitis is difficult to diagnose. A 48-year-old Hispanic female presented with a 4-day history of abdominal pain and a vaginal cuff tear requiring laparoscopic repair. She subsequently developed postsurgical disseminated HSV, resulting in ALF. Acyclovir was initiated, but she was resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…In addition, Herpes viruses such as Epstein–Barr virus (EBV), Cytomegalo virus (CMV), Adenovirus and Varicella zoster virus (VZV) also induce hepatic injury ( Lalazar and Ilan, 2014 ). Herpes simplex virus (HSV) induced hepatitis is a rare cause of acute liver failure ( Chaudhary et al, 2017 ).…”
Section: Antiviral Effect Of Zinc On Hepatitis Virusesmentioning
confidence: 99%
“…In addition, Herpes viruses such as Epstein–Barr virus (EBV), Cytomegalo virus (CMV), Adenovirus and Varicella zoster virus (VZV) also induce hepatic injury ( Lalazar and Ilan, 2014 ). Herpes simplex virus (HSV) induced hepatitis is a rare cause of acute liver failure ( Chaudhary et al, 2017 ).…”
Section: Antiviral Effect Of Zinc On Hepatitis Virusesmentioning
confidence: 99%
“…Діарея серед наших пацієнтів була другим за частотою порушенням функції ШКТ. За даними опублікованих досліджень, діарея серед пацієнтів з тяжким перебігом гострих захворювань зустрічається в 11-78 % випадків [17][18][19][20][21] [27][28][29]. За опублікованими даними, у пацієнтів з вітряною віспою зростання АЛТ виявлялось у 50,9 %, підвищення білірубінуу 20 % [27], підвищення АЛТ спостерігалось у 14 % хворих з HSV-інфекцією, при EBV-інфекції помірне зростання АЛТ та ЛДГ -у 90 % випадків, підвищення ЛФ -у 60 % і білірубіну -у 45 % [30].…”
Section: обговоренняunclassified
“…These two agents inhibit the catalytic unit of viral DNA polymerase and do not require activation by thymidine kinase [21]. Chaudhary et al reported one case of HSV hepatitis that showed no improvement with acyclovir, but when foscarnet was added the patient’s mental status improved and she was ultimately discharged home with no need for liver transplantation [22]. Other important questions to consider with regards to treatment are the optimal route of administration (intravenous vs oral) and the subsequent duration of therapy.…”
Section: Reviewmentioning
confidence: 99%